Uganda : Policy, Participation, People - World Bank (Washington, DC, 2012)
When the government of President Museveni assumed power in Uganda in 1986, it took over a shattered postwar economy. Market-oriented reforms led to a remarkable recovery. International Development Association (IDA) operations in Uganda initially tackled economic recovery, rehabilitation, and stabilization, then turned slowly to institutional and private sector development as the country stabilized. Since 1995, IDA has focused on poverty reduction and social progress. An OED (Operations Evaluation Department) assessment of IDA assistance to Uganda during 1987-99 found that IDA has excelled at policy dialogue, economic and sector work (ESW), and fostering participatory processes; had signal success in mobilizing resources and debt relief; and broadened the stakeholder dialogue on aid coordination. There is room for improvement, however, in some aspects of project implementation. The Bank and other donors were involved on a very high plane in Uganda, and important successes were achieved, partly because of the government's strong political leadership, its eagerness to learn from experience, its good use of technical assistance in core government agencies, and its recognition of the need to deepen its commitment and broaden the ownership of reform.